Roles of Fiscal Policy in New Zealand - Felicity C Barker; Robert A Buckle; Robert W St Clair (New Zealand Government, The Treasury, 2008)
Economic growth is one of the objectives of the current government. Fiscal policy, encompassing government expenditure and taxation decisions, can significantly impact on economic growth. This paper proposes a framework which views fiscal policy through three lenses and applies this approach to consider how fiscal policy affects economic growth. The three lenses are: fiscal sustainability, fiscal structure and fiscal stabilisation. The paper reviews international literature pertaining to these three lenses and discusses the extent to which these lenses are incorporated into New Zealand's current fiscal framework. Contemporary New Zealand fiscal challenges are discussed and, in light of these challenges, the paper concludes with consideration of areas to investigate which may yield improvements to the New Zealand fiscal framework.
Keywords: E6; E61; E62; E63; 330; Fiscal policy; sustainability; stability; structure; taxation; government spending; economic growth; Finanzpolitik; Nachhaltigkeit; Öffentliche Ausgaben; Öffentliche Einnahmen; Wirtschaftswachstum; Neuseeland